City Branding and City Identity Research: A Bibliometric Review - Muhammad Rana Al Rizqi; Syamsul Hidayat (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to map the intellectual structure and scholarly development of city branding and city identity research through a bibliometric approach. The review draws on a dataset of 100 articles published between 2015 and 2025, accumulating 4,887 citations, indicating strong academic visibility and impact within this domain. Bibliometric mapping was conducted using keyword co-occurrence and citation analysis through VOSviewer, enabling the visualization of thematic networks across the literature. The results highlight city branding as the most central and dominant keyword, functioning as a conceptual hub that links major research themes such as city image, identity, tourist, and perception. The network structure reveals strong associations between city branding and city image, suggesting that image formation constitutes one of the most frequently examined outcomes in city branding research. Furthermore, the linkage between city image and city identity confirms a recurring conceptual pathway in which city image operates as a mediating construct in the process of identity construction. Additional findings indicate an emerging emphasis on implementation-related dimensions, reflected by nodes such as role, process, practice, and challenge, which highlight practical obstacles including message consistency, visual identity integration, and stakeholder engagement. Overall, the study demonstrates that city branding extends beyond promotional activities and operates as a multidimensional strategic system connecting identity articulation, symbolic communication, governance mechanisms, stakeholder experiences, and the consolidation of city identity and reputation.